2019
DOI: 10.1002/hep.30241
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Role of Hepatocyte Cyclooxygenase‐2 Expression Against Liver Ischemia–Reperfusion Injury in Mice

Abstract: These data support the view of a novel protective effect of hepatic COX-2 induction and the consequent rise of derived prostaglandins against IRI. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 48 publications
5
43
0
1
Order By: Relevance
“…Excessive production of reactive oxygen species in the early phase of reperfusion is another critical factor in hepatic I/R injury [26, 27]. Some prior researches have indicated that the activation of antioxidative enzymes and antioxidants significantly ameliorated hepatic I/R injury [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive production of reactive oxygen species in the early phase of reperfusion is another critical factor in hepatic I/R injury [26, 27]. Some prior researches have indicated that the activation of antioxidative enzymes and antioxidants significantly ameliorated hepatic I/R injury [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10% of early graft failure cases are caused by I/R injury, and the incidences of acute and chronic rejection are higher . Moreover, with the rising demand for organs and steady improvement in immunosuppression strategies, an increasing number of marginal donors, who are more susceptible to I/R injury, will be used . Although great efforts have been made to explore a treatment strategy to alleviate acute liver I/R injury, no strategy has been proven to be absolutely effective in clinical practice .…”
mentioning
confidence: 99%
“…(3) Moreover, with the rising demand for organs and steady improvement in immunosuppression strategies, an increasing number of marginal donors, who are more susceptible to I/R injury, will be used. (4) Although great efforts have been made to explore a treatment strategy to alleviate acute liver I/R injury, no strategy has been proven to be absolutely effective in clinical practice. (5,6) Therefore, more insights into the mechanism of injury and therapeutic measures will need to be developed.…”
mentioning
confidence: 99%
“…In concanavalin A (ConA) induced liver injury model, depleted COX2 in mice accelerated liver injury 24 . Hepatocyte COX2 expression protected against liver ischemia-reperfusion injury (IRI), meanwhile, in patients underwent liver transplantation, there was a signi cant positive correlation of plasma PGE 2 levels and graft function 25 . These results indicated that PGE 2 might have great therapeutic potentials in treating in ammatory liver diseases.…”
Section: Discussionmentioning
confidence: 99%